Uncovering the Meaning of Judicial Power as a Legal Goal in The Maqasid Syari’ah Perspective (Lembaga Contrarius Indonesia, 2026)
The meaning of judicial power as a discourse in every discussion is always linked to the natural law theory pioneered by Thomas Aquinas. However, this natural law theory, which emphasizes the discourse of judges as representatives of God from a practical perspective, needs to be elaborated to foster understanding in legal practice. The appreciation of carrying out this task is very important, because the word judge (hakim, Indonesian) is taken from the word Al Hakiim (Arabic), one of the 99 names of Allah in Asmaul Husna which means the Most Wise. This study, therefore, presents the idea of Maqashid Syariah which contains the meaning of wisdom as a methodology in implementing the concept of judicial power. This research uses normative legal research methods with a hermeneutical approach. This research resulted in the conclusion that the responsibility of implementing the concept of judicial power for a judge in order to produce just laws requires the participation of conscience as a fatwa provider regarding what is right and wrong, in addition to reason. The Maqasid Syariah approach in the context of interpreting judicial power in this research recommends that it is important for policy makers to take steps that are in line with efforts to maintain the mind, religion, soul, lineage and assets of judges in order to maintain their independence in carrying out their duties.